Calculus : early transcendentals - Anton, Howard, 1939-; Bivens, Irl, ....-; Davis, Stephen L., 1952- (Hoboken : Wiley, 2010)
The ninth edition continues to provide engineers with an accessible resource for learning calculus. The book includes carefully worked examples and special problem types that help improve comprehension. New applied exercises demonstrate the usefulness of the mathematics. Additional summary tables with step-by-step details are also incorporated into the chapters to make the concepts easier to understand. The Quick Check and Focus on Concepts exercises have been updated as well. Engineers become engaged in the material because of the easy-to-read style and real-world examples.
Keywords: Differentiaalrekening; Integraalrekening; Lineaire algebra